Scientific Progress of Research on Extracorporeal Cardiopulmonary Resuscitation: A Scientometric Analysis of Global Publications (Revista de Medicina Clinica, 2024)
Introduction: Understanding trends and scientific progress of extracorporeal cardiopulmonary resuscitation (ECMO), as well as current knowledge gaps and opportunities for transformative innovation, considering the context of researchers and institutions worldwide, is essential for the continued advancement of these procedures, which significantly reduce mortality rates. The aim of this study was to provide data on the global scientific progress of ECMO research. Materials and Methods: This was a bibliometric study based on scientific information deposited in Scopus database. Results: 12,218 scientific documents were included. The scientific production predominantly consisted of original articles (75.47%; n=9221), followed by reviews (8.92%; n=1090). Identified international collaboration was 11.9%. The United States (n=5035) and the AP-HP Assistance Publique - Hôpitaux de Paris (France; n=281) were the most prolific country and institution, respectively. This same country possesses the largest global collaboration network, and one of its institutions, the University of Michigan, has established itself as the most robust institution and one of the most important reference centers. Particularly notable is the research on treatment outcomes, survival, cohort analyses, and different age groups. Conclusions: This study revealed in a novel way the investigative patterns and scientific progress of global ECMO research.
Keywords: Extracorporeal Membrane Oxygenation; Cardiopulmonary Resuscitation; Biomedical Research; Bibliometrics